Remote-Controlled Laboratories of Experimental Physics: Measuring the Stiffness of a Spring - Ahmed, AL Sabri; Yassine, Khazri; Mohamed, Moussetad; Youness, Akensous; Ahmed, Fahli; Mohamed, AL Amoudi (Transactions on Engineering and Computing Sciences, 2017)
In modern E-Learning, students and scientists will be able to access Web portals for scientific computer and data infrastructures, thus accessing large collections of data and digital objects using metadata, knowledge management techniques, and specific data services. Students will apply existing scalable Web and grid technologies to access and share scientific data, using educational and computing resources to run scientific Practical exercises. Such an approach will allow the creation of enriched interactive through a real devices and real remote mechanisms that interactively support the exploration of scientific phenomena. Advanced repository and collaboration services will allow students to remotely and securely up- and download science and engineering learning objects. E-lab is essentially created to realize experiments by interacting with real devices that are real remote mechanisms, through an appropriate telecommunications platform, equipped with a dedicated management system and a number of software interfaces and material. Our works is aiming to : Measurement of the rigidity of a spring. This method translator pedagogical experiences and turn them into reality at an affordable, expand research sources to students.